Effect of addition of graphene nanoplatelets on the mechanical properties of triaxially braided composites. (4th March 2023) - Marrivada, Gayatri Vineela; Chaganti, Phaneendra Kiran; Sujith, Ravindran; Sharma, Bhavika
Abstract : Braided composites possess an advantage of good out-of-plane mechanical properties, near net-shape manufacturing, impact and damage resistance. This work aims to investigate the effect of graphene nanoplatelet (GNP) addition on glass fibre triaxial braided composites (TBC). Tensile, flexural, and short beam shear tests were conducted to investigate the mechanical performance of the pristine and hybrid TBC. A numerical model was framed to estimate the material properties of hybrid TBC which were further used as input for the finite element simulation. Results indicate a 15% increase in tensile strength, a 20% increase in flexural strength and a 10% increase in interlaminar shear strength (ILSS). The experimental results were in good agreement with the analytical results. The braided architecture along with proposed GNP combination further enhances mechanical properties and enables gradual failure of the composite which is a desirable property for load bearing structures.